A Study of Consumer Awareness Regarding Pharmaceutical Industries: Examining Consumer Awareness and Perceptions in the Pharmaceutical Sector (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This study aims to examine consumer awareness regarding pharmaceutical industries and theimplications for healthcare decision-making. Consumer awareness plays a crucial role in shapingperceptions and choices related to pharmaceutical products and services. However, limited research hasfocused on understanding consumer knowledge, attitudes, and behaviors in this context. Through acomprehensive literature review and analysis of existing data, this study provides valuable insights intoconsumer awareness levels, gaps, and factors influencing consumer perceptions of pharmaceuticalindustries. The findings will contribute to the development of targeted strategies and initiatives aimed atimproving consumer education, transparency, and trust in the pharmaceutical sector.